A Web-Based Instrument for Infantile Atopic Dermatitis Identification (Electronic Version of the Modified Child Eczema Questionnaire): Development and Implementation - Heping Fang; Lin Chen; Juan Li; Luo Ren; Yu Yin; Danleng Chen; Huaying Yin; Enmei Liu; Yan Hu; Xiaoyan Luo (JMIR Publications, 2023)
BackgroundAtopic dermatitis (AD) is a chronic inflammatory cutaneous disease that affects 30.48% of young children; thus, there is a need for epidemiological studies in community settings. Web-based questionnaires (WBQs) are more convenient, time-saving, and efficient than traditional surveys, but the reliability of identifying AD through WBQs and whether AD can be identified without the attendance of doctors, especially in community or similar settings, remains unknown. ObjectiveThis study aimed to develop and validate a web-based instrument for infantile AD identification (electronic version of the modified Child Eczema Questionnaire [eCEQ]) and to clarify the possibility of conducting WBQs to identify infantile AD without the attendance of doctors in a community-representative population. MethodsThis study was divided into 2 phases. Phase 1 investigated 205 children younger than 2 years to develop and validate the eCEQ by comparison with the diagnoses of dermatologists. Phase 2 recruited 1375 children younger than 2 years to implement the eCEQ and verify the obtained prevalence by comparison with the previously published prevalence. ResultsIn phase 1, a total of 195 questionnaires were analyzed from children with a median age of 8.8 (IQR 4.5-15.0) months. The identification values of the eCEQ according to the appropriate rules were acceptable (logic rule: sensitivity 89.2%, specificity 91.5%, positive predictive value 97.1%, and negative predictive value 72.9%; statistic rule: sensitivity 90.5%, specificity 89.4%, positive predictive value 96.4%, and negative predictive value 75%). In phase 2, a total of 837 questionnaires were analyzed from children with a median age of 8.4 (IQR 5.2-14.6) months. The prevalence of infantile AD obtained by the eCEQ (logic rule) was 31.9% (267/837), which was close to the published prevalence (30.48%). Based on the results of phase 2, only 20.2% (54/267) of the participants identified by the eCEQ had previously received a diagnosis from doctors. Additionally, among the participants who were not diagnosed by doctors but were identified by the eCEQ, only 6.1% (13/213) were actually aware of the possible presence of AD. ConclusionsInfantile AD can be identified without the attendance of doctors by using the eCEQ, which can be easily applied to community-based epidemiological studies and provide acceptable identification reliability. In addition, the eCEQ can also be applied to the field of public health to improve the health awareness of the general population.